Teachers Efforts to Improve Student Literacy in Islamic Cultural History Subjects - Novita, Yanti; Yulianti, Vira; Handayani, Delvina; Sugestina, Eva (Khalifa Journal of Islamic Education, 2022)
Literacy is one of the most important instruments in advancing a country's education, not even in Indonesia.Â  Research from developed countries has encouraged learners to access, understand, and use things intelligently through activities, such as reading, seeing, listening, writing, and speaking. In the Islamic education facility, even literacy is a duty for any Muslim, as the first Quran verse encourages Muslims to always be studious. It is precisely this research aimed at learning about the efforts of educators, particularly teachers of the history of Islamic culture, in improving literacy among educated people. The study used a qualitative method with a case study design approach. The data source was drawn from the three informants through deep interviews chosen using impressive sampling techniques. All the informers were teachers of the history of Islamic culture. The entire interview was analyzed thematically using nvivo software 12. Research shows the four attempts made by teachers to improve learners' literacy. The four are i) perform cooperative or group learning, ii) perform oral tests, iii) provide school reading or madding, and iv) make a ten-minute reading movement before beginning the lesson. The four attempts of teachers in this study can be set as an example for teachers in the history of Islamic culture, and schools to improve literacy cultures among learners.